2022
DOI: 10.3389/fendo.2022.785674
|View full text |Cite
|
Sign up to set email alerts
|

Animal Foetal Models of Obesity and Diabetes – From Laboratory to Clinical Settings

Abstract: The prenatal period, during which a fully formed newborn capable of surviving outside its mother’s body is built from a single cell, is critical for human development. It is also the time when the foetus is particularly vulnerable to environmental factors, which may modulate the course of its development. Both epidemiological and animal studies have shown that foetal programming of physiological systems may alter the growth and function of organs and lead to pathology in adulthood. Nutrition is a particularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 291 publications
(421 reference statements)
0
6
0
Order By: Relevance
“…72 Second, it is important to investigate various "ART-DOHaD" animal models, produced by ART and shown to exhibit longterm effects, 73 integrated into "DOHaD" animal models produced by maternal nutritional imbalance such as under-and overnutrition. 74 Since ART in domestic animals including cattle, sheep, and horses is worldwide used, pre-and peri-natal effects have been studied to resolve ART-associated problems such as low pregnancy rates, prolonged gestation, and fetal overgrowth, also known as the large offspring syndrome (LOS). 73 As a result of studying causative factors, for example, for LOS in cattle, which presents as an aberrant development of the placenta, 75 the inclusion of serum in embryo culture medium and co-culture with oviductal cells were identified mainly to cause abnormal feto-placental development in ruminants.…”
Section: Perinatal and Long-term Outcomes Associated With Ivf/ivcmentioning
confidence: 99%
See 1 more Smart Citation
“…72 Second, it is important to investigate various "ART-DOHaD" animal models, produced by ART and shown to exhibit longterm effects, 73 integrated into "DOHaD" animal models produced by maternal nutritional imbalance such as under-and overnutrition. 74 Since ART in domestic animals including cattle, sheep, and horses is worldwide used, pre-and peri-natal effects have been studied to resolve ART-associated problems such as low pregnancy rates, prolonged gestation, and fetal overgrowth, also known as the large offspring syndrome (LOS). 73 As a result of studying causative factors, for example, for LOS in cattle, which presents as an aberrant development of the placenta, 75 the inclusion of serum in embryo culture medium and co-culture with oviductal cells were identified mainly to cause abnormal feto-placental development in ruminants.…”
Section: Perinatal and Long-term Outcomes Associated With Ivf/ivcmentioning
confidence: 99%
“…First, it is important to study animals presenting mutations involved in the regulation of placental development, in particular those causing intrauterine growth restriction and pre‐eclampsia, 71 as well as mutant animals with type 2 diabetes mellitus and obese phenotypes such as ob / ob mice 72 . Second, it is important to investigate various “ART‐DOHaD” animal models, produced by ART and shown to exhibit long‐term effects, 73 integrated into “DOHaD” animal models produced by maternal nutritional imbalance such as under‐ and overnutrition 74 . Since ART in domestic animals including cattle, sheep, and horses is worldwide used, pre‐ and peri‐natal effects have been studied to resolve ART‐associated problems such as low pregnancy rates, prolonged gestation, and fetal overgrowth, also known as the large offspring syndrome (LOS) 73 .…”
Section: Effects Of In Vitro Culture On Future Healthmentioning
confidence: 99%
“…Taste preferences and the susceptibility to obesity in an obesogenic environment depend on the genotype [ 7 , 8 ] and the conditions of early life of individuals [ 9 ]. It has been shown that in utero environments have a significant effect on the predisposition of offspring to develop obesity later in life [ 10 ], and this effect can significantly differ in offspring of different sexes [ 11 , 12 ]. Maternal obesity and a maternal high-calorie diet during pregnancy and lactation were shown to increase the risk of obesity development in offspring [ 13 , 14 ] and to affect offspring calorie intake and taste preferences [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Offspring born to CAF mothers have altered body weight and fat content, as well as glucose, insulin, leptin, and triglyceride levels. However, the results of metabolic outcomes vary depending on the used paradigm (e.g., duration of the diet, its contents, time of exposure to the diet), animal species, and sex of offspring (see review [13]).…”
Section: Introductionmentioning
confidence: 99%